Algunos datos para la historia del Palacio de Vista Alegre en Carabanchel Bajo - Díaz Miguez, Daniel (Anuario del Departamento de Historia y Teoría del Arte, 1998)
Amongst the numerous Royal Family possesions in the 19th century, there’s one which has been mostly overlooked: Vista Alegre estate, at Carabanchel Bajo. It was a place, similar to those many aristocratic families owned in the surroundings of Madrid. María Cristina and her daughters used to go there to rest and to enjoy a bucolic way of life near nature. We ignore how and when they got hold of the estate country, but we contribute some really interesting maps that show its magnitude, the different sorts of countryside buildings, the diverse outside games... and also they let us know better their way of life. From these accounts we may catch a glimpse of Martín López Aguado’s authorship, of Pascual and Colomer’s participation and of the different repairs in the estate along the years. We’ve got a better knowledge of the functions of the Royal House, and we can get a close look at the incomes and expenses they got from cropping at this possession. Later on, the country estate was bought by the Marquis of Salamanca who, when he died, left substantial debts that made the building go to public hands (nowadays it belongs to Comunidad of Madrid).